Evaluation the Effect of the Health Promoting Lifestyle by Multimedia Education on Sexual Function in Women With Multiple Sclerosis - Masoomeh Kheirkhah; Azadeh Ahadi; Seyed Massood Nabavi; Najmeh Tavakkol; Tayebeh Lotfi (Iran University of Medical Sciences, 2022)
Background & Aims: Multiple sclerosis is the most common progressive neurological disease in young people and affects women several times more than men. Sexual problems are one of the most common symptoms in affected women, which have a great impact on the couple's relationship and are often ignored. Therefore, the present study aimed to determine the effect of health-promoting multimedia education on sexual function in women with multiple sclerosis. Materials & Methods: The present study is a randomized controlled trial of before and after with the control group. 116 women with multiple sclerosis, referredto Hazrat Rasool Akram Hospital and a private referral center for multiple sclerosis patients (from 21 September 2020 to 19 January 2021) were selected by continues sampling method to participate in the study. They were assigned as two groups, intervention and control ones, using the Sealed envelope randomized online site which randomly divided to single up to quintuple blocks, which allocated equally in intervention and control groups. Data collection tools were demographic profile form and intimacy and sexual activity questionnaire for multiple sclerosis patients (MSISQ-19). Data analysis is done by using descriptive statistical methods (mean, standard deviation, frequency and percentage) and with independent t-test, chi-square, analysis of covariance and analysis of variance with repeated measures RM using SPSS software v. 16. Results: Before the intervention, there was no significant difference between the two groups in terms of sexual function scores and all its dimensions (P=0.690). Mean sexual function in the intervention group at 4 weeks (P=0.014) and 12 weeks after the intervention (P=0.021) was significantly lower than before, but there was no statistically significant difference between the scores at 4 weeks and 12 weeks after the intervention (P<0.050). Conclusion: Health-promoting lifestyle (HPL) training has an effect on sexual performance of women with multiple sclerosis and this training can be a good way to improve their sexual problems.